Effect of anion in carboxylate-based ionic liquids on catalytic activity of transesterification with vinyl esters and the solubility of cellulose. Issue 7 (31st January 2019) - Hirose, Daisuke; Wardhana Kusuma, Samuel Budi; Nomura, Shuhei; Yamaguchi, Makoto; Yasaka, Yoshiro; Kakuchi, Ryohei; Takahashi, Kenji
Abstract : The role of 1-ethyl-3-methylimidazolium carboxylate-type ionic liquid as the solvent and organocatalyst for transesterification reaction of cellulose was investigated. Abstract : The role of 1-ethyl-3-methylimidazolium (Emim) carboxylate-type ionic liquid (IL) as the solvent and organocatalyst for transesterification reaction of cellulose was investigated. The reported method using Emim acetate and vinyl ester caused an undesired side reaction: the acetate anion derived from EmimOAc was introduced into cellulose ester. To improve the reaction system, ILs with a high cellulose solubility, a high degree of substitution (DS) value, and low side-reaction were systematically explored. Newly synthesized Emim p -anisate and a mixed solvent system achieved the transesterification reaction of cellulose with a high DS value derived from the employed vinyl esters (DS > 2.9), and a low DS value derived from side reaction (selectivity > 99%).